Extreme Temperatures, Hospital Utilization and Public Health Insurance Spending - Yusun Kim; Qing Miao; Ling Zhu (International Journal of Public Health)
ObjectivesThis study examines the impact of extreme temperatures on hospital utilization and public health insurance program spending in a country with no universal health coverage.MethodsUsing nationwide U.S. county-level panel data and a fixed effects model, we estimate the impact of annual variations in the number of hot and cold days on hospital utilization and medical reimbursements for low-income and elderly beneficiaries of public health insurance.ResultsOur results show that extreme heat and mild cold increase medical reimbursements to low-income beneficiaries, while extreme cold increases benefit transfer to the elderly. We find that extreme temperatures have particularly stronger positive effect on hospital admission and inpatient care utilization among old and poor patients. The fiscal impact of extreme temperatures is greater in areas with more generous income eligibility criteria for public health insurance.ConclusionThe study advances our understanding of how extreme temperatures affect healthcare utilization of low-income and elderly populations and the roles public health insurance plays in supporting them from increasing weather risks. Our findings suggest that climate change can augment the financial burden on governments.